Experimental investigation of shape memory polymer hybrid nanocomposites modified by carbon fiber reinforced multi-walled carbon nanotube (MWCNT). (29th October 2021) - Markad, Kanif; Lal, Achchhe
Abstract: This paper presents the effect of the variations of multi-walled carbon nanotube (MWCNT) modification in shape memory polymer hybrid composites concerning their mechanical, thermomechanical, and shape memory characterizations. The process of fabrication includes preparation of the MWCNT/epoxy hybrid nanocomposites by shear mixing, ultrasonication, magnetic stirring, and subsequent molding by hand layup method. The appropriate post-processing was performed for the curing and cutting to prepare the samples for the mechanical and thermomechanical characterizations as per the ASTM standards. An enhancement in the thermomechanical properties was noticed due to the incorporation of the MWCNT. These observations were also validated with improvement in the interfacial bonding between the carbon fiber and the modified matrix, as shown in the morphological fractography. The tensile strengths were improved by 18%, 39%, and 26% with the incorporation of 0.4%, 0.6%, and 0.8% modified MWCNT nanocomposites as compared to pure unmodified SMPC. However, the shape recovery of all the configurations of the shape memory polymer hybrid composites was not compromised on polymer-modified remaining almost unchanged at 94%.